International Study Group of Pancreatic Surgery type 3 and 4 venous resections in patients with pancreatic adenocarcinoma:the Paoli-Calmettes Institute experience. Issue 10 (October 2019) - Al Faraï, Abdallah; Garnier, Jonathan; Ewald, Jacques; Marchese, Ugo; Gilabert, Marine; Moureau-Zabotto, Laurence; Poizat, Flora; Giovannini, Marc; Delpero, Jean-Robert; Turrini, Olivier
Abstract: Introduction: A new neoadjuvant regimen, together with more aggressive surgeries, appears to have increased the resectability rate in patients with pancreatic ductal adenocarcinoma (PDAC). Our study aimed to evaluate the outcomes of patients who underwent venous resection (VR) during pancreatectomies for PDAC. Materials and methods: Between 2005 and 2017, 130 patients underwent pancreatectomies with type 3 or 4 (i.e., segmental resection without or with graft interposition, respectively) VR for PDAC. Patients' characteristics, surgical techniques, perioperative management, pathological findings, and outcomes were recorded and compared during 2 inclusion periods: the landmark year for the introduction of the FOLFIRINOX regimen and the hyperspecialization of our pancreatic-surgery team was 2010. Results: Performance of pancreatectomies with VR steadily increased through the 2 inclusion periods. In the overall series (n = 130), the median overall survival time and the 5-year survival proportion were 26.3 months and 21%, respectively. Upon multivariate analysis, ASA score 3 ( P = 0.01) and R1 resection margins ( P < 0.01) were found to be negative independent factors influencing survival. Patients who underwent upfront VR (n = 47) had survival rates similar to those of patients who received neoadjuvant treatment (n = 83). After 2010, more complex VR were performed; however, no difference was found between the 2 periods with respect to postoperative courses, pathologic findings, or survival after a matching process based on patients' characteristics and tumor stages. Conclusion: Over the last 2 decades, VR during pancreatectomy has been confirmed as a safe procedure despite the increase in technical complexity. Disappointingly, we did not observe any dramatic survival improvement.